Implemantasi Aplikasi Kahoot sebagai Media Pembelajaran Interaktif dengan Siswa SMP Negeri 1 Kunto Darussalam - Irwan Hidayat; Anik Supriani; Agung Setiawan (Departement of Mathematics Education, 2023)
The use of technology and databases is starting to be in great demand by educators in the learning process. This technological advancement requires the ability of teachers to adapt, master and have competence in using technological tools to support the learning process. Digital technology is expected to be used to improve the quality of learning, by utilizing digital technology it is hoped that it can attract and increase students' learning motivation in learning. One of the technological innovations so that learning becomes conducive, interactive, interesting and can help teachers make evaluations of assessments of students is using the Kahoot platform. Kahoot is a game-based interactive learning media that is easily accessible and user friendly. One of the learning media that can be used in an effort to increase student learning motivation is by implementing digital gamification learning media that is packaged with educational-based online games, one of which is by implementing the Kahoot application which is one of the learning media. The purpose of this study was to determine the implementation of the Kahoot application in increasing student motivation. The method used is to use qualitative research with a literature study and field study approach, with subjects and research objects at Pasundan Banjaran High School. The results of the study stated that by implementing the Kahoot application as a learning medium it created interest and also the learning motivation of Pasundan Banjaran high school students increased drastically so that the expected learning competencies were achieved.